Sepakbola Eropa dan Multikulturalisme: Sebuah Pendekatan Analitis pada Keterlibatan Pemain Sepakbola Keturunan Imigran di Persepakbolaan Eropa sebagai Refleksi Keberagaman di Masyarakat Eropa - Alifsar Nurfauzi; Muhammad Rizky Mahendra; Febry Amanda Rizky Putra (Jurnal Sentris, 2022)
The involvement of immigrant descent footballers has become an important phenomenon for the demographic changes in the world, partially Europe. This phenomenon has reflected multiculturalism and heterogeneity in European society. The inclusion of foreign footballers into national teams has become common which leads to denationalisation of European national football teams, but the dynamics and complexities have remained under-researched. In this research, we will use the paradigm of constructivism to see Europe as a world society constructed by shared identities and values. This research will analyse how diversification and multiculturalism represented by football in nine countries who heavily impacted by immigrants could shape heterogeneity in European society. The results depict that the existence of immigrant descent footballers reflect the multiculturalism and heterogeneity of the European society.